The Effect of Entrepreneurship Education and Self-Efficacy on Entrepreneurial Motivation of STIE Eka Prasetya’s Students - Pesta Gultom; Wany Wany; Alvin Alvin (Enrichment : Journal of Management, 2021)
The purpose of this study is to determine the effect of Entrepreneurship Education, and Self-Efficacy on Entrepreneurial Motivation of STIE Eka Prasetya’s students partially and simultaneously. The population used in this study were all students of STIE Eka Prasetya who already had a business independently, totaling 147 people. Data were collected by distributing online questionnaires via google form with a total sample of 107 respondents. Analysis of the data used is statistical analysis in the form of multiple linear regression test. The results of this study indicate that partially and simultaneously the variables of Entrepreneurship Education, and Self- Efficacy have an effect on Entrepreneurial Motivation of STIE Eka Prasetya’s students. This is evidenced by the results of the simultaneous test (F test) and the results of the partial test (t test), and also it shows the significant values of the two independent variables that support the hypothesis. Therefore, the test results from this study state that there is a simultaneous influence between the variables of Entrepreneurship Education, and Self-Efficacy on Entrepreneurial Motivation of STIE Eka Prasetya’s students, and the effect is 49%, this is evidenced by the determination test.